Antibodies Against the Clock Proteins Period and Cryptochrome Reveal the Neuronal Organization of the Circadian Clock in the Pea Aphid - Colizzi, Francesca Sara; Beer, Katharina; Cuti, Paolo; Deppisch, Peter; Martínez Torres, David; Yoshii, Taishi; Helfrich-Förster, Charlotte (Frontiers in Physiology, 2021)
Circadian clocks prepare the organism to cyclic environmental changes in light, temperature or food availability. Here, we characterized the master clock in the brain of a strongly photoperiodic insect, the aphid Acyrthosiphon pisum, immunohistochemically with antibodies against A. pisum Period (PER), Drosophila melanogaster Cryptochrome (CRY1) and crab Pigment-Dispersing Hormone (PDH). The latter antibody detects all so far known PDHs and PDFs (Pigment-Dispersing Factors), which play a dominant role in the circadian system of many arthropods. We found that, under long days, PER and CRY are expressed in a rhythmic manner in three regions of the brain: the dorsal and lateral protocerebrum and the lamina. No staining was detected with anti-PDH, suggesting that aphids lack PDF. All the CRY1-positive cells co-expressed PER and showed daily PER/CRY1 oscillations of high amplitude, while the PER oscillations of the CRY1-negative PER neurons were of considerable lower amplitude. The CRY1 oscillations occurred highly synchronous in all neurons, suggesting that aphid CRY1 is similar light-sensitive and its oscillations synchronized by light-dark cycles as is true for Drosophila CRY1. Nevertheless, in contrast to Drosophila CRY1, aphid CRY1 was not degraded by light, but steadily increased during the day and decreased during the night. PER was always located in the nuclei of the clock neurons, while CRY was predominantly cytoplasmic and revealed the projections of the PER/CRY1-positive neurons. We traced the PER/CRY1-positive neurons through the aphid protocerebrum discovering striking similarities with the circadian clock of Drosophila melanogaster: the CRY1 fibers innervate the dorsal and lateral protocerebrum and putatively connect the different PER positive neurons with each other. They also run toward the pars intercerebralis, which controls hormone release via the neurohemal organ, the corpora cardiaca. In contrast to Drosophila, the CRY1-positive fibers additionally travel directly towards the corpora cardiaca and the close-by endocrine gland, corpora allata. This suggests a direct link between the circadian clock and the photoperiodic control of hormone release that can be studied in the future.